Disability and School Enrollment in Indonesia: A Comparative Analysis - Nur Hidayati; Dwini Handayani; Prita Nurmalia Kusumawardhani (Didaktika: Jurnal Kependidikan, 2026)
This study aims to analyze the relationship between disability and school participation opportunities and identify the source of school participation gaps between children with disabilities and non-disabilities. The data used came from the National Socio-Economic Survey (Susenas) in March 2021, with a Linear Probability Model analysis approach. The estimated results showed that children with disabilities had a lower chance of attending school by 13,57% compared to non-disabled children, meaning that there was a statistically significant difference. These findings indicate a marked gap in school participation between the two groups. Follow-up analysis using the Blinder-Oaxaca decomposition with non-disabilities as a reference group showed that about 15,34% of the gap in school participation could be explained by differences in observable characteristics. In contrast, most of the gaps, which were about 84,66%, came from differences in coefficients and unexplained factors. These results confirm that the unexplained component plays a dominant role in explaining the inequality of school participation between children with and without disabilities.